Comparison of Compudose®, Ralgro® and Synovex-C® for suckling steer calves - D.D. Simms; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1984)
The comparative growth-promoting value of Compudose, Ralgro, Ralgro + Ralgro reimplant, and Synovex-C + Synovex-C reimplant was evaluated on five Kansas ranches with 674 suckling steer calves in seven trials conducted during 1982 and 1983. The Ralgro + Ralgro reimplant program increased gain significantly (P<.05) over controls, with an average improvement of 3.9%. Either a single Ralgro or Compudose implant at branding increased gain about 2.6%. Implanting with Synovex-C produced 1% improvement in gain.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Implants; Gain; Growth